Development of perovskite-based light emitting diodes with improved stability 3.0 - Goh, Hubert Qing Yao (Nanyang Technological University, 2020)
Many electrical devices in evolving quantities, low-cost and high-capacity pollutants have been associated in the display industry. Perovskite LEDs can be conveniently tuned to create different colors, leading to greater sensitivity, high performance and lower costs by improvements to the atomic composition of the perovskite structure and hence become the in-market demand in the display industry. However, there is a pressing issue with the quantum dots of perovskite which caused instability when induced by the strong delocalization of surface ions. Cesium lead halide perovskite nanocrystals (CsPbX3) can emits light faster and stronger than traditional illumination materials. Nanocrystals formed by lead halide perovskites can also emits specific coloured light across a spectrum of visible wavelengths by substituting either with Iodine or Bromine or Chlorine. These factors make them excellent and suitable for making LEDs. Hence, this project served to discuss and explore the development of the perovskite quantum dots with improved stability and a series of experiments were carried out.